Efectos de las estrategias interactivas en los logros de aprendizaje de los estudiantes de secundaria de la Institución Educativa N° 60528 Hermanos Palla, Intuto 2022 - Amias del Aguila, Carlos Alberto (2022)
The research had the following general objective: Determine the Learning Achievements before and after the application of the interactive strategies of the Secondary School students of the Educational Institution No. 60528 Hermanos Palla, Intuto 2022. The research was of a correlational type. The general design used was that of the experimental investigation of the pre-experimental type. The population was made up of 343 students from Educational Institution No. 60528 Hermanos Palla, Intuto 2022. The sample consisted of 76 Secondary Education students from Educational Institution No. 60528 Hnos. Palla 2022. The selection of the sample, drawn from the sample design for populations of less than 1,500. The data collection instrument that was used was the questionnaire and the pre and posttest that had the purpose of knowing the learning achievements of the students of the Educational Institution No. 60528 Hnos. Palla 2022 before and after the application of interactive strategies. The most important results are: tc = 33.30; tt = 2.82; df = 9; ? = 1%, concluding that the Learning Achievements before and after the application of the interactive strategies have a statistically significant difference in the Secondary School students of the Educational Institution No. 60528 Hermanos Palla, Intuto 2022. Therefore, the hypothesis is accepted. research hypothesis: "Learning Achievements will have a statistically significant difference before and after the application of interactive strategies in Secondary School students of Educational Institution No. 60528 Hermanos Palla, Intuto 2022".